Efektivitas dan Akuntabilitas Penyelenggaraan Bantuan Keuangan Khusus (BKK) Dana Keis-timewaan pada Kalurahan di DIY Tahun Anggaran 2021-2023 - Herlina Ahan; Kusharyanti; Januar Eko Prasetio (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to evaluate the accountability and efficacy of the Special Financial Assistance (BKK) Special Funds implementation in villages within the Special Region of Yogya-karta (DIY) during the fiscal year 2021–2023.  Additional govern-ing authority is provided by the passage of Law Number 13 of 2012 regarding the Special Region of DIY, which is backed by the distribution of Special Funds.  Through the BKK plan, these pay-ments have been disbursed directly to village councils since 2021 as a way to decentralise the exercise of special authority.  The four stages of management—planning, implementation, administra-tion, and reporting/accountability—are the subject of this study, which employs a qualitative descriptive methodology. The study's findings indicate that a strong internal control system, participa-tory planning, and human resource preparedness all have a signifi-cant impact on how well BKK is implemented.  In the meantime, issues with information transparency and reporting consistency continue to plague accountability for implementation.